2013
DOI: 10.1080/03091929.2012.657190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a deep flow on a surface boundary current

Abstract: International audienceThe stability properties of a coastal current composed of a deep flow and of an intense counterflowing surface jet are investigated with a linear quasi-geostrophic model and with a nonlinear isopycnic shallow-water model (MICOM), both in three-layer configurations. The currents are modeled by strips of uniform potential vorticity anomaly (PVA), with opposite signs. The linear stability analysis of the current is performed with exponentially-growing modes, varying the ratio of layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…not a motionless ocean. The addition of mean flow to the surrounding ocean is supported by results from high‐resolution ocean models (Petersen et al , ) as well as by the modifications in the instability of ocean currents that override a lower layer with mean flow (Meunier et al , ). Dewar and Killworth () showed that a Gaussian eddy in a shallow‐water model is stable when the underlying ocean co‐rotates with the eddy itself with a fairly strong tangential velocity so that the vertical shear is significantly reduced (i.e.…”
Section: Introductionmentioning
confidence: 89%
“…not a motionless ocean. The addition of mean flow to the surrounding ocean is supported by results from high‐resolution ocean models (Petersen et al , ) as well as by the modifications in the instability of ocean currents that override a lower layer with mean flow (Meunier et al , ). Dewar and Killworth () showed that a Gaussian eddy in a shallow‐water model is stable when the underlying ocean co‐rotates with the eddy itself with a fairly strong tangential velocity so that the vertical shear is significantly reduced (i.e.…”
Section: Introductionmentioning
confidence: 89%
“…The impact of eddies on the formation and growth of filaments from coastal fronts was also observed in satellite imagery by Shapiro et al [2010] in the Black sea and by Serra et al [2010] in the southern Iberian upwelling system. Moreover, most processes recognized to trigger the filamentation of a front are associated with vortical structures, whether they originate from topographic effects [ Meunier et al , 2010; Barton et al , 2004], instability processes [ Ikeda and Emery , 1984; Marchesiello et al , 2003; Capet and Carton , 2004; Meunier et al , 2012] or external sources [ Strub et al , 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Many numerical studies have focused on the dynamics of upwelling filaments, highlighting the variety of physical processes possibly responsible for their formation and evolution. The formation of steep meanders through intrinsic baroclinic instability of the upwelling front was investigated by Ikeda and Apel [1981], Ikeda et al [1989], Haidvogel et al [1991], Batteen [1997], Capet et al [2002], Marchesiello et al [2003], Capet and Carton [2004], Batteen et al [2007], and Meunier et al [2012]. They all agreed in the meander‐like nature of the filaments, but some studies differed on the role of the coast‐line geometry and the bottom topography especially in the trapping of the filaments.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Stability of flows in multilayer models has been considered in a number of studies (see summary for three‐layer rectilinear QG flows in Table 1 by Olascoaga []). The growth rate of baroclinic instability was noticed to be sensitive to an intermediate layer with uniform PV between upper and deep flows [e.g., Sutyrin , ; Meunier et al ., ]. Instability of a circular QG vortex has been analyzed by Sokolovskiy [] where the problem generally depends on eight nondimensional parameters.…”
Section: Introductionmentioning
confidence: 99%